Transition-Metal-Free С–С Coupling of 5,7-Dihydroxybenzopyrones with Quinoxalones and Pteridinones - Khalymbadzha, Igor A.; Fatykhov, Ramil F.; Chupakhin, Oleg N.; Charushin, Valery N.; Tseitler, Tatiana A.; Sharapov, Ainur D.; Inytina, Anna K.; Kartsev, Victor G. (Synthesis, 2018)
A new synthetic protocol for nucleophilic substitution of hydrogen in quinoxalones and pteridinones by the action of 5,7-dihydroxycoumarins and related m-dihydroxybenzene compounds has been developed. The C–C coupling reaction proved to proceed smoothly under rather mild conditions, thus giving the corresponding C–H functionalized products in good yields. The advantages of this environmentally benign protocol are high regio- and chemoselectivity, and an easy workup procedure. Direct incorporation of the coumarin moiety into the pyrazine ring in pteridines or quinoxalines provides a short pathway to pyrazine-coumarin hybrid compounds.
Keywords: metal-free coupling; halogen-free coupling; pteridines; quinoxalines; C–H arylation; substitution of hydrogen